Сhanges in bacterial keratitis grade 2 in patients with diabetes mellitus (Ukrainian Journal of Ophthalmology, 2025)
Background: The pathological changes in the immune system and inflammatory response in diabetes mellitus (DM) result in impaired wound healing and the chronicity of the immune response.Purpose: To determine the features of the longitudinal changes in bacterial keratitis grade 2 in patients with type 1 DM.Material and Methods: We retrospectively reviewed the outcomes of treatment of 19 patients (19 eyes; main group) with both bacterial keratitis grade 2 and type 1 DM and 15 patients (15 eyes; control group) with bacterial keratitis grade 2 only. All patients received topical antibiotic, ofloxacin. In addition, they received topical antiseptics, antioxidants, repairing agents, hyaluronic acid-based artificial tears, and mydriatics and systemic anti-inflammatory agents. Observations were performed within 24 days after initiation of treatment. Patients had a routine eye examination, bacteriological studies, fluorescein dye test, anterior eye OCT and non-contact corneal esthesiometry.Results: Compared to the controls, patients of the main group showed increased corneal sensitivity within the study period, increased corneal infiltrate depth and corneal edema depth beginning from day 3, and increased severity of pericorneal injection and corneal ulcer depth beginning from day 7 (р < 0.05). In addition, corneal infiltrate resolved in all patients of the main group four days later and corneal edema, seven days later than in controls (р < 0.05). Most patients of the main group had a more severe outcome than did controls. Particularly, on day 24, an ulcer defect was still present in 33.3% of patients of the main group, with corneal haze, nubecula corneae and macula corneae seen in 44.4% and 22.2%, respectively, of patients of this group, versus 93.3% and 6.7%, respectively, for controls (р < 0.05).Conclusion: The features of the longitudinal changes in bacterial keratitis grade 2 in patients with DM cause prolongation of the course and worsening of outcomes of therapeutic treatment of bacterial keratitis grade 2.
Keywords: diabetes mellitus; bacterial keratitis; severity of bacterial keratitis; longitudinal changes in bacterial keratitis